THE CREEDAL VIEWS OF PSEUDO-SALAFISM AND THEIR IDEOLOGICAL AFFINITY WITH HISTORICAL TASHBIH MOVEMENTS (The Journal of Interdisciplinary Human Studies, 2026)
This article conducts a comparative analysis of the creedal positionsadvanced by contemporary pseudo-Salafi movements and their ideological affinity withthe historical mushabbiha and mujassima sects of Islamic intellectual history. Despitepseudo-Salafis’ self-presentation as defenders of pure creed, the article demonstratesthat their doctrinal roots lead back to the deviant sects of earlier Islamic history. Fiveprincipal areas of ideological convergence are identified: the literal interpretation ofmutashabih Qurʼanic expressions; the attribution of direction and locality to Allah;the attribution of movement and change to Allah; the rejection of taʼwil combined withfalse attribution to the pious ancestors; and the use of takfir ideology. The article furtheridentifies the Karramiya sect of Muhammad ibn Karram al-Sijistani (d. 255/868) asthe historical movement most closely aligned with contemporary pseudo-Salafism. Thestudy concludes that pseudo-Salafism represents not a continuation of the methodologyof the genuine pious ancestors but a modern revival of the doctrinal positions of thehistorically deviant mushabbiha, mujassima, and Karramiya movements, and that thecritiques formulated by Imam al-Maturidi and Imam Abu al-Muʿin al-Nasafi remaindirectly applicable to their contemporary positions.
Keywords: pseudo-Salafism; mushabbiha; mujassima; Karramiya; tajsim; tashbih; Islamic creed; taʼwil; tafwid; Maturidism; Ashʿarism; takfir; Ibn Taymiya; Wahhabism; Uzbekistan.